The Relevance Of Translations Of Gafur Gulyam's Works Into Russian (Eurasian Journal of Learning and Academic Teaching, 2024)
The article reflects the difficulties of translating the works of Ghafur Ghulam from Uzbek into Russian. When translating, it is important not only to convey the essence of the work, but also the whole range of impressions of the original language. The close connection with the culture and biography of the writer allows you to convey into Russian all the feelings that the writer wanted to convey to the reader. Russian Russian speaker Gafur Gulyam's work is in demand, which is a formative factor for the translation of the writer's works into Russian.